Perkütan Koroner Girişim Uygulanan Hastalarda Müzik ve Doğa Seslerinin YaşamBulguları ve Anksiyete Düzeyleri Üzerine Etkisi - OĞUZ, SIDIKA (My University, 2022)
Araştırmada Perkütan Koroner Girişim yapılan hastalarda işlem öncesi dinletilen makam müziği, klasik müzik ve doğa seslerinin yaşam bulguları ve anksiyete üzerine etkisini değerlendirmek amaçlandı. Araştırma Kasım 2019 – Eylül 2020 tarihleri arasında gerekli izinler alınarak yapıldı. Araştırma ön test-son test, kontrol gruplu deneysel çalışma olarak planlandı. Araştırmanın evrenini araştırmanın yapıldığı tarihlerde hastanelerin kardiyoloji servislerinde yatan Perkütan Koroner Girişim yapılacak koroner kalp hastaları, örneklemi ise araştırma kriterlerine uygun ve araştırmaya katılmayı kabul eden hastalar oluşturdu. Araştırma 52 deney, 52 kontrol grubu olmak üzere toplam 104 hastayla yapıldı. Veriler “Anket Formu” ve “Durumluk ve Sürekli Kaygı Envanteri” kullanılarak toplandı. Verilerin analizi bilgisayar ortamında istatistiksel analizler yapılarak değerlendirildi. Deney grubu hastaların işlem öncesi ve işlem sonrası yaşam bulguları incelendiğinde solunum ve sıcaklık ortalamaları arasında anlamlı bir fark vardı (p<0,01). Deney grubu hastaların işlem öncesi Durumluk Kaygı Envanteri puan ortalaması 62,2±4,0, işlem sonrası 59,2±3,8 olduğu ve deney grubunun işlem sonrası kaygılarının azaldığı saptandı (p<0,001). Kontrol grubu hastaların işlem öncesi Durumluk Kaygı Envanteri puan ortalaması 62,7±3,1, işlem sonrası 61,1±4,3 olduğu ve aralarında anlamlı bir fark olmadığı bulundu (p>0,05). Makam müziği ve doğa sesleri dinleyen hastaların işlem sonrası Durumluk Kaygı Envanteri puan ortalamalarının düştüğü ve kaygılarının azaldığı belirlendi (sırasıyla; p<0,01, p<0,001). Klasik müziğin işlem sonrası hastaların durumluk kaygı düzeylerini etkilemediği saptandı (p>0,05). Makam müziği, klasik müzik ve doğa seslerini dinleyen deney grubunun işlem öncesi sürekli kaygı düzeyinin kontrol grubuna göre daha düşük olduğu belirlendi (p<0,01). Makam müziği, klasik müzik ve doğa sesleri Perkütan Koroner Girişim öncesi hastaların kaygısını azalttı. Müzik ve doğa sesleri kalp hastaları için kullanılabilecek uygulanabilir, maliyeti olmayan, invaziv girişim gerektirmeyen etkin bir yöntemdir.

In this study, the evaluation of the effects of maqam music, classical music and nature sounds on anxiety and vital signs in patients who underwent Percutaneous Coronary Intervention was aimed. The research was conducted between November 2019 and September 2020, with the necessary permissions which were obtained beforehand. The research was planned as a pretest-posttest, experimental study with a control group. The population of the study consisted of coronary heart patients who were hospitalized in the cardiology services of the hospitals at the time of the study, and the sample consisted of patients who met the research criteria and who accepted to participate in the study. The research was conducted with a total of 104 patients, who were distributed to the experiment and control groups as 52 participants each. Data was collected using a "Questionnaire" and the "State and Trait Anxiety Scale". The analysis of the data was evaluated by performing statistical analysis on the computer. When the vital signs of the patients who were in the experimental group were examined before and after the procedure, a significant difference was found between their respiratory and temperature averages (p<0,01). The average score of the State Anxiety Inventory regarding the patients in the experimental group before the procedure was 62.2 ± 4.0, while after the procedure it was 59.2 ± 3.8 and therefore, a decrease was found in terms of the anxiety of the experimental group (p<0,001). Before the procedure, the mean State Anxiety Inventory score of the control group patients was 62.7 ± 3.1 whereas after the procedure it was 61,1±4,3 and therefore, no significant difference was found between them (p>0,05). It was determined that the mean State Anxiety Inventory scores, alongside with the anxiety of the patients who listened to maqam music and nature sounds decreased after the procedure (respectively; p<0,01, p<0,001). It was found that classical music did not affect the state anxiety levels of the patients after the procedure (p>0,05). It was determined that the trait anxiety levels of the experimental group listening to maqam music, classical music and nature sounds before the procedure was lower than the anxiety levels of the control group (p<0,01). Before Percutaneous Coronary Intervention, maqam music, classical music and nature sounds decreased the anxiety of the patients. It was concluded that the aforementioned types of music and sounds were an effective, suitable, cost free and non-invasive method which can be used for heart patients.
The effect of music and nature sounds on vital findings and anxiety levels in patients with percutaneous coronary intervention
Keywords: Anxiety; Music; Nature sounds; Percutaneous coronary intervention; Anksiyete; Doğa sesleri; Müzik; Perkütan koroner girişim